Investing in Education: Pakistan as a Traditional Society in a Modern World (Journal of Education and Educational Development, 2020)
Developing countries have seen a direct influence of foreign playerson their educational policies. This influence of foreign players on thePakistani educational policy has been direct and prominent after 9/11attacks. This paper looks into the effectiveness of money spent by thedonor nations to malign the effect of Islamization in the Pakistanisociety. This research was conducted taking into consideration theideas that investment in the Pakistani education sector by foreigndonors have not westernized the Pakistani youth and that there is nodifference between the perception of the Pakistani youth and theirparents with regard to culture and religion. The sample selectedconsisted of 120 youngsters aged between 16 to 18 years of age.A questionnaire consisting of 17 yes/no questions was used tocollect the required data. The results from the research showed that thefamily structure in Pakistan was half way between traditional andwestern. There were certain things that the Pakistani youth understoodas an essential part of their lives, and there was no compromise on thetraditional values, whereas there were other things that the youthconsidered less important and these were steadily disappearing fromtheir set of traditional values.
Keywords: human capital theory, modernization, traditional society, western society; human capital theory; modernization; traditional society; western society